AuSi molecule revisited: IOTC/CASSCF/CASPT2 calculations. Issue 5 (14th October 2020) - Barysz, Maria; Černušák, Ivan; Kellö, Vladimir; Neogrády, Pavel
Abstract: The results of theoretical calculations for the ground and low‐lying excited states of the AuSi molecule are presented. Calculations were carried out using the spin‐free relativistic infinite‐order two‐component (IOTC) Hamiltonian in conjunction with the multistate CASPT2 method. For comparison, the ground state was also calculated using the IOTC‐CCSD(T) method. The spin‐orbit coupling is introduced via the restricted active space state interaction method with the use of the atomic mean‐field SO integrals. The results are compared with the available experimental and theoretical results. The spectroscopic parameters derived from the potential energy curves are presented. The results obtained suggest that the experimental data should be reconsidered. Abstract : We present, for the first time, full potential energy curves and the corresponding spectroscopic parameters of the ground state and selected numbers of the excited states of the AuSi molecule. All theoretical results consistently show that the ground‐state thermochemical experimental dissociation energy value is not correct and should be reconsidered. We show that the relativistic IOTC method works well in molecular calculations and, additionally, that we do not have to make very complicated calculations because the small active space already allows us to obtain quite good results.